2013
DOI: 10.1063/1.4793201
|View full text |Cite
|
Sign up to set email alerts
|

Investigate the role of the active layers' structures and morphology in the performance of the organic solar cell devices

Abstract: Several CuPc/PTCDI-C8 films with different structures (co-deposited, layered, and bilayer) were prepared and their structural properties were studied using X-ray diffraction. In order to study the effects of the active layers' structures on the performance of the device, organic solar cells based on these films were fabricated and their electrical characteristics have been explored. Absorbed prominent diffraction peaks for CuPc/PTCDI-C8 bilayer films indicate the formation of higher degree of crystallinity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…20) With this background, we focused on the thin film heterostructure of copper phthalocyanine (CuPc), a representative p-type organic semiconductor material, on N,N'-Di-noctyl-3,4,9,10-perylenetetracarboxylic diimide (PTCDI-C8), a promising non-fullerene n-type organic semiconductor 21) with a high electron mobility of 1.7 cm 2 V −1 s −1 . 22) It is because this material combination can be a model system of the existing stacked structures consisting of n-alkyl perylene diimides and CuPc as p-n junction solar cells 23,24) or photodetectors, 25) though their structural information has scarcely been reported in detail so far. In this study, it was found that PTCDI-C8 which was vapor-deposited at relatively high temperatures formed large grains with an average size of a few hundred micrometers with a molecularly flat grain surface.…”
Section: Introductionmentioning
confidence: 99%
“…20) With this background, we focused on the thin film heterostructure of copper phthalocyanine (CuPc), a representative p-type organic semiconductor material, on N,N'-Di-noctyl-3,4,9,10-perylenetetracarboxylic diimide (PTCDI-C8), a promising non-fullerene n-type organic semiconductor 21) with a high electron mobility of 1.7 cm 2 V −1 s −1 . 22) It is because this material combination can be a model system of the existing stacked structures consisting of n-alkyl perylene diimides and CuPc as p-n junction solar cells 23,24) or photodetectors, 25) though their structural information has scarcely been reported in detail so far. In this study, it was found that PTCDI-C8 which was vapor-deposited at relatively high temperatures formed large grains with an average size of a few hundred micrometers with a molecularly flat grain surface.…”
Section: Introductionmentioning
confidence: 99%
“…These improvements are mainly explained by the increased interfacial area at which a donor (p-type) and an acceptor (n-type) materials form an intimate contact and where the charge transfer between two materials takes place. [13][14][15][16] Accordingly, such a structure is thought to enhance the dissociation of excitons at interfaces. However, random structural phases in a BHJ layer may disrupt the transport of generated charge carriers, because there is possibility of clusters that are not well electrically connected to the other clusters.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally agreed in organic PV (including dye-sensitized solar cells) that the energetics of the D/A interface define a theoretical upper limit to the open-circuit voltage (V OC ) via the ionization energy (IE) of the donor and the electron affinity (EA) of the acceptor, and because of the dependence of the short-circuit current density (J SC ) of the solar cell on the difference between the EA values of the D and A materials [1][2][3][4][5][6][7][8] . Morphology of active layers [10][11][12] , orientation and electronic interaction 13 between D and A material can also influence solar cell parameters. The missing 0.3 eV has been a point of discussion and many reasons like exciton binding energy 2 , band gap states 9 has been suggested for it.…”
Section: Introductionmentioning
confidence: 99%
“…3 The difference of 0.3 eV has been a point of discussion and many reasons such as the exciton binding energy, 2 and band gap states 9 have been suggested for it. The morphology of active layers, [10][11][12] orientation and electronic interaction 13 between D and A materials can also inuence solar cell parameters. The crystallinity in D and A materials is crucial for the photo-induced charge separation efficiency at the DA interface.…”
Section: Introductionmentioning
confidence: 99%